Seksualitas Pelajar Hindu Pada Masa Brahmacari Di Kota Denpasar (Perspektif Komunikasi) - Ida Ayu Made Purnamaningsih (Jayapangus Press, 2018)
The sexuality of Hindu students during the Brahmacari period is very alarming. Brahmacari holistically is the order of the cultural values of the noble Hindu Religion, seen in the present day tend to experience the decline of meaning. Evident from the number of HIV / AIDS 2014 increased by 2.37% survey results Denpasar Health Department. Hindu students should abstain from sexual intercourse during their studies. The process of communication from various related agencies has been done in Denpasar City, but the phenomenon of sexual deviation is still rife happening. This study explores three problem formulas; (1) the factors that influence the deviation of sexuality among Hindu students; (2) interpersonal communication in the practice of Hindu student sexuality; (3) the potential emancipation of brahmacari values among Hindu students.